Mechanisms of T cell evasion by Epstein-Barr virus and implications for tumor survival - Sausen, D. G.; Poirier, M. C.; Spiers, L. M.; Smith, E. N. (Frontiers in Immunology, 2023)
Epstein-Barr virus (EBV) is a prevalent oncogenic virus estimated to infect greater than 90% of the world's population. Following initial infection, it establishes latency in host B cells. EBV has developed a multitude of techniques to avoid detection by the host immune system and establish lifelong infection. T cells, as important contributors to cell-mediated immunity, make an attractive target for these immunoevasive strategies. Indeed, EBV has evolved numerous mechanisms to modulate T cell responses. For example, it can augment expression of programmed cell death ligand-1 (PD-L1), which inhibits T cell function, and downregulates the interferon response, which has a strong impact on T cell regulation. It also modulates interleukin secretion and can influence major histocompatibility complex (MHC) expression and presentation. In addition to facilitating persistent EBV infection, these immunoregulatory mechanisms have significant implications for evasion of the immune response by tumor cells. This review dissects the mechanisms through which EBV avoids detection by host T cells and discusses how these mechanisms play into tumor survival. It concludes with an overview of cancer treatments targeting T cells in the setting of EBV-associated malignancy.